Pleiotrophe Effekte von Statinen (3-Hydroxy-3-Methylglutaryl-Coenzym A-Reduktasehemmer) - Igel, Michael; Sudhop, Thomas; Bergmann, Klaus von (Arzneimittelforschung, 2003)
Pleiotrophic Effects of Statins (3-Hydroxy-3-methylglutaryl-coenzyme A Reductase Inhibitors)The development of statins improved the therapy of hypercholesterolemia and atherosclerotic disease tremendously. The beneficial effects of statins were clearly demonstrated in large scale primary and secondary prevention studies. In addition to the reduction of plasma cholesterol, inhibition of 3-hydroxy-3-methylglutaryl-coenzyme A (HMG-CoA) reductase also results in the depletion of intermediates of cholesterol biosynthesis that are important for cellular integrity. The so called pleiotrophic effects of statins and probably also their adverse events can be attributed to the inhibition of synthesis of these intermediates. The review article describes the pathogenesis of atherosclerosis, the pharmacokinetic and pharmacodynamik of statins, and their pleiotrophic effects concerning endothelial function, LDL (low density lipoprotein) oxidation, macrophages, smooth muscle cell proliferation, atherosclerotic plaque, platelets, thrombosis, proinflammatory factors, haemorheology, hypertension, venous thrombosis, bone metabolism, stroke, and the possible influence on the prevention of Alzheimer’s disease.
Keywords: 3-Hydroxy-3-methylglutarylcoenzyme A reductase inhibitors; Statins, effect on atherosclerosis, effect on cholesterol, pleiotrophic effects